Elevated brain natriuretic peptide (BNP) is an early marker for patients at risk for complications after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS + HIPEC). Issue 4 (28th November 2017) - Fisher, Sarah B.; Rafeeq, Safia; Hess, Ken; Grotz, Travis E.; Mansfield, Paul; Royal, Richard; Badgwell, Brian; Fleming, Jason; Fournier, Keith; Mann, Gary N.
Abstract : Background: Elevated BNP is associated with adverse cardiac outcomes after noncardiac surgery. We assessed BNP values as markers of perioperative fluid status and their correlation with major/cardiopulmonary (CP) complications following CRS + HIPEC. Methods: Fluid balance, BNP levels, and morbidity data were collected for all patients undergoing CRS + HIPEC between 6/2014 and 2/2016. Results: One hundred and twenty‐nine patients underwent CRS + HIPEC for appendiceal adenocarcinoma ( n  = 99), mesothelioma ( n  = 16), and colon cancer ( n  = 14). Less than 10% had CP comorbidities. The median PCI was 14 (range 4‐39); 89% underwent CC0/1 resection ( n  = 115). Median blood loss (EBL) was 497 mL (50‐2700). Major complications (Clavien III‐V) occurred in 16 (12%), CP in 17 (13%), and major/CP in 24 (18%). Thirty‐day mortality occurred in 2 (1.5%). Elevated BNP on POD1 correlated with increased risk of major/CP complications (OR 2.2, P  = 0.052). This was most pronounced in the 25 patients receiving cisplatin: for each 100 unit increase in POD1 BNP the OR for major/CP complication was 7.4 versus 1.2 for the remaining patients, P  = 0.083. Multivariate analysis identified increased EBL (OR 4.1 P  = 0.011) and a trend toward increased BNP on POD1 (OR for each 100 unit increase 2.0, P  = 0.10) as risk factors for major/CP complications. Conclusions: Postoperative BNP measurement after CRS + HIPEC may guide postoperative fluid resuscitation and facilitate identification of patients at risk for major and/or cardiopulmonary complications.